THE PLACE AND IMPORTANCE OF TIRE MUSEUM IN THE PRESERVATION OF CULTURAL LEGACY - Ayşegül KOYUNCU OKCA (Fırat University, 2019)
Culture is defined as a whole of tangible and intangible products that communities pass on socially from generation to generation, as a collection of symbolic and learnt products or traits; the complete traits of human activities socially conveyed. However, cultural heritage is all sorts of concrete or abstract mobile or immobile entities which inform about the history and culture of a country or region. City museums examine the identies forming the city, the city's ethnic, cultural and artistic components.Besides , they are the buldings which primarily study the way of living, the city's historical turning points, its location and relations with its neighbours on the basis of changing and developing. In fact, they are the buildings based on the narration from generation to generation, not the ones based on the works which examine the past with the future together. In short, they draw attention to the importance and place of the material cultural elements in culture rather than the material cultural elements themselves. The most important trait making a city a city is the protection of its values that have witnessed all the adventures the city has brought from the past to to the present day. Among the duties and responsibilies of the city museums is the reminding of vanishing city memory. In this study, Tire Museum, a beautiful example of city museums, will be promoted, not only being contented with the exhibition of folkloric and ethnographic stuffs of Tire Museum, but the efforts of introducing traditional occupation bearing cultural legacy quality to our day, sustaining them and making the future generations benefitting from them will also be mentioned. Field studies have been conducted in order to acquire the data required for the realisation of this study and necessary information has been obtained by using observation and interview techniques in the light of method understanding.In addition, literature scanning has been fulfilled and this study has been depended on scientific basis. The traditional occupation which are tried to be introduced at Tire Museum have been photoghraphed and documented by us.